The Relationship Between Physical Activity, Lipid Profile, and Two New Anthropometric Cardiovascular Risk Factors Among Men - Mojtaba Amirabadizadeh; Mohammad Esmaeil Afzalpour; Tooba Kazemi (Gonabad University of Medical Sciences, 2020)
Background: Cardiovascular diseases are among the most prevalent causes of morbidity and mortality. This research investigated the relationship between physical activity, lipid profile, and new anthropometric cardiovascular risk factors among men. Methods: This cross-sectional study was conducted on 155 adult men (30-50 years old) who were selected randomly from 250 men called by public announcement. Standard methods were used to measure their anthropometric indices and then they were asked to complete the Baecke questionnaire. ANOVA was used to compare basic anthropometric and clinical characteristics in different age groups followed by Tukey's posthoc test. A correlation of anthropometric measurements with glucose and lipid parameters was determined by the Pearson correlation coefficient. P<0.05 was considered as a significant level.  Results: The Mean ±SD age of the participants was 39.8±0.5 years. Their Mean±SD Body Mass Index (BMI) was 25.6±0.3 kg/m2 with a Mean±SD Neck Circumference (NC) of 38.4±0.1 cm, and Mean±SD Wrist Circumference (WRC) of 17.4±0.0 cm. There was a statistically significant difference between age groups concerning height, BMI, WRC, and Fasting Blood Glucose (FBG). The NC showed statistically significant correlation with weight (r=0.7, P<0.001), triglyceride (r=0.1, P=0.033), High-Density Lipoprotein (HDL) (r=-0.2, P=0.007) and Physical Activity (PA) (r=-0.1, P=0.020). Also the WRC had statistically significant correlation with weight (r=0.7, P<0.001), height (r=0.1, P=0.021) and HDL (r=-0.1, P=0.024). Conclusion: Measuring NC like other methods was a potential assessment tool of cardiovascular risk factors and can be used for epidemiological studies. Also, WRC had no significant relation. However, WRC's negative correlation with HDL was very important and can indicate the health status of individuals.